Can Guided Discovery Instruction Be Detrimental to Children with Different Levels of Aquatic Competence in Infancy? - Juan Antonio Moreno-Murcia; Luciane de Paula-Borges; Alfonso Trinidad (MDPI AG, 2024)
Repetitive practice can become an exploratory activity where instruction and discovery are linked, allowing instruction and guidance through tasks that help to construct and acquire the knowledge and skills that make up the content. (1) Background: The aim of the study was to show how a teaching method based on guided discovery would affect the teaching of children's aquatic competence in schoolchildren with different levels of competence. (2) Methods: An observational study was conducted with 385 schoolchildren (195 boys and 189 girls) aged 3-5 years belonging to a charter kindergarten, using an Instrument for the Measurement of Aquatic Competence in Children (SMACC) consisting of 17 items grouped into three dimensions: socio-affective, cognitive, and motor. (3) Results: After measuring aquatic competence, all age groups and all variables (motor, cognitive, and socio-affective) showed differences between pre- and post-scores and a high magnitude of effect size. When the teaching intervention was analyzed according to the level of aquatic competence of the age group, improvements were found in all variables in both the low and high-competence groups. (4) Conclusions: This study describes how guided discovery instruction has equal effects at different levels of proficiency. Furthermore, when this type of instruction was used, aquatic competence was explained not only by the motor and socio-affective dimensions but also by the cognitive variable.